PERFORMANCE OF KENBRO CHICKEN FED COWPEA (Vigna unguiculata): SOYBEAN (Glycine max) DIETS AT VARIOUS REPLACEMENT LEVELS - Katumo, Mulwa Albert; Mworia, Dr. Mugambi; Ncene, Dr. William (IJRDO- Journal of Educational Research, 2017)
The demand for poultry meat has tremendously over the years, and the high cost of Soybean meal necessitates the evaluation of locally available protein ingredients which can be used as substitutes for conventional protein meals. This research sough to study the effect of substituting Soybean meal with Cowpea meal on feed intake, weight gain, feed conversion ratio and cost per kg weight gain in Kenbro chicks. The results showed that there was no significant difference in feed intake, while there was a significant difference in total weight gain (g), and feed conversion ratio. There was equally no significant difference production cost of one kg live weight and thus the study concludes that Cowpea meal can replace up to 50 % SBM (14 % of the diet) as an alternative cheaper plant protein source in Kenbro diets at 3-9 weeks of age this can be an excellent source of dietary protein.